Letramentos e etnografia: reflexões sobre os efeitos secundários do letramento - Araújo, Erika Maria Santos de (2019)
The purpose of this work is, through the rescue of significant stories and events, to present reflections on the side effects of literacy. At the beginning of the research, in march of 2017 school year, the main question was: what can be done, in terms of Portuguese language teaching, that may be meaningful to my students from the perspective of social literacy? However, as time went by, my research changed course. I began to move away from a positivist path, in which the intention is to look for a problem and solve it, and I turned my attention to the side effects of my practice that suddenly appeared in march 2018. Thus, through ethnography and its methods of record generation, I started a rescue of my practice and the search for understanding these effects. To support the analysis of these effects, I used the theoretical basis of Braga (2015), Buzato (2009; 2015), Gomes (2015; 2016), Mey (1998), Rajagopalan (2003), Rojo and Moura (2012), Gomes (2019), Hooks (2017), Bourdieu (2015), Hall (2015), Certeau (2014), Foucault (2017) and Milton Santos (2013). To build the reflections I selected three side effects: (1) Peter's case; (2) Bruna's case and (3) Gustavo's case. Therefore, opposing to the view of autonomous model, where language is understood only as a mere skill and the social implications of literacy are always peaceful, this research shows how literacy hás a function in society, a means of functioning that inspires our attitudes towards the society.